G GEOLOGI DAN KARAKTERISTIK GUNUNG LUMPUR ( MUD VOLCANO ) SUBDISTRIK OESILO, DISTRIK OECUSSE, TIMOR LESTE: GEOLOGI DAN KARAKTERISTIK GUNUNG LUMPUR ( MUD VOLCANO ) SUBDISTRIK OESILO, DISTRIK OECUSSE, TIMOR LESTE - Santi Viandi, Mardiana (Retii, 2024)
ABSTRACTThe Research Setting Is Administratively Located At Oesilo Sub-District, Oecusse, East Timor.The Research Aimed At Figuring Out The Characteristics Of Oesilo Mud Volcano In Terms OfMaterials Content, Physical Appearance, And Formation Process Which Then Compared WithThe Surrounding Geological Condition. The Lithology Of Research Setting Is Composed OfLimestone In The Age Of Upper Miocene (N15) – Pliocene (N18). Geological StructureBecomes The Factor Or The Primary Causal For The Emergence Of Mud Volcano At Oesilo,Oecusse. It Is Anticline Structure Which Then Involved In Fault Processes Named Bend 1 And 2Normal Right Slip Fault Directed To North And South, As Well As Native Normal Slip FaultDirected To East-West. The Analyses On Xrd, Water, Petrography, And Paleontology ReportedThat All Six Mud Volcanoes Have The Same Source Of Mud. The Materials Exhaled By ThemAre Dense Mud And Gas, Mud With Water, Gas, And Stone Fragment. The Fossil Analysis OnThe Mud Indicated That The Exhaled Mud Materials Are Categorized Old. Thin Section OnSome Stone Fragments Expelled Showed The Fossil Content Of Globegerinoides ObliquusbolliIn The Age Of Upper Miocene – Pliocene.Keywords: Mud Volcano, Tear Faults, Oesilo, East Timor